Determinants of sleepiness at work among railway control workers. (January 2017) - Cotrim, Teresa; Carvalhais, José; Neto, Catarina; Teles, Júlia; Noriega, Paulo; Rebelo, Francisco
Abstract: In the last two decades the control of the Portuguese railway network has become much more centralized in three centres, there integrating the functions of route flow management, electrical control and signalling. This study aimed to investigate the influence of work and individual determinants in sleepiness among railway control workers, namely socio-demographic factors, work ability, psychosocial factors, shiftwork characteristics, fatigue perception, and sleep. Sleepiness by shift was associated with quality of sleep, job satisfaction, fatigue perception, quantitative demands, and age. The results indicate a high prevalence of sleepiness during the night shift and show the relevance of the quality of sleep as a predictor in the three models of sleepiness for morning, afternoon and night shifts. This study, done at the major Portuguese railway control centre, alerted managers to the importance of schedule planning as well as sleepiness prevention plans and makes these results a reference for future research. Highlights: High prevalence of sleepiness during the night shift among the railway control workers. Sleep quality was a significant predictor of sleepiness for the three shifts. Job satisfaction, quantitative demands, fatigue perception and age also influenced sleepiness.